2013
DOI: 10.1093/nar/gkt182
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA loc285194 is a p53-regulated tumor suppressor

Abstract: Protein-coding genes account for only a small part of the human genome, whereas the vast majority of transcripts make up the non-coding RNAs including long non-coding RNAs (lncRNAs). Accumulating evidence indicates that lncRNAs could play a critical role in regulation of cellular processes such as cell growth and apoptosis as well as cancer progression and metastasis. LncRNA loc285194 was previously shown to be within a tumor suppressor unit in osteosarcoma and to suppress tumor cell growth. However, it is unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
313
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(319 citation statements)
references
References 48 publications
5
313
0
1
Order By: Relevance
“…Moreover, in vivo studies confirmed that LOC285194 can bind to and downregulate MIR211. 64 Thus LOC285194 may modulate the cancer phenotype through its function as an endogenous miRNA sponge. Additionally, a reciprocal repression feedback loop exists between LOC285194 and MIR211, suggesting that miRNAs can also modulate lncRNAs.…”
Section: Role Of Lncrnas In Tumorigenesis and Progressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, in vivo studies confirmed that LOC285194 can bind to and downregulate MIR211. 64 Thus LOC285194 may modulate the cancer phenotype through its function as an endogenous miRNA sponge. Additionally, a reciprocal repression feedback loop exists between LOC285194 and MIR211, suggesting that miRNAs can also modulate lncRNAs.…”
Section: Role Of Lncrnas In Tumorigenesis and Progressionmentioning
confidence: 99%
“…Additionally, a reciprocal repression feedback loop exists between LOC285194 and MIR211, suggesting that miRNAs can also modulate lncRNAs. 64 In this scenario, lncRNAs and miRNAs may interact as components of a new genomic regulatory network, thereby greatly expanding the functional genetic information in the human genome.…”
Section: Role Of Lncrnas In Tumorigenesis and Progressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al reported that lncRNA loc285194, a known lncRNA in osteosarcoma, is a p53 transcription target with two binding sites of miR-211 in its exon 4. The ectopic expression of loc285194 suppressed tumor cell growth in vitro and in vivo by repressing miR-211-induced cell growth [77]. Recently, Hu et al reported that lincRNA GAPLINC was overexpressed in GC tissues and correlated with poor survival of patients with GC.…”
Section: Lncrna Interacts With Protein and Mirnamentioning
confidence: 99%